The 21st century learning: incorporating heutagogical approach and digital information literacy / Azma Asnawi Abd Hakim ... [et al.] - Abd Hakim, Azma Asnawi; Hashim, Husain; Mohamed Shuhidan, Shamila; Mohamed Shuhidan, Shuhaida (UiTM Press, 2019)
The world of education has been revolutionary since the past three decades. Ranging from research on how people learn, to the studies on how teaching could and should be provided (Hase & Kenyon, 2013), education will continue to adapt to the growing needs of the societies. Over the years, it has been viewed from the pedagogical perspective of the relationship between the educator (teacher, lecturer and instructor) and the learner (student). It is always a linear and sequential process of learning in the way that the educator is in full control to decide on what the learner need to know, and certainly, how the knowledge and skills should be taught. Most recently, as dynamism and flexibility of the 21st century is connected to the emerging digital and social media era, and as immeasurable information flows directly to the fingertips of everyone, it gives a huge impact to teaching and learning, as well as to the growth of complex workplace needs.